Pandemi Covid-19: Inflasi dan Pengangguran Dalam Perspektif Ekonomi Islam - Hasanah, Mauizhotul (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
This study aims to analyze the tradeoff between inflation and unemployment based on an Islamic economic perspective. Inflation and unemployment are important indicators of economic performance and both are major problems that must be controlled immediately because they will have a wide impact on various things, especially during the Covid-19 pandemic conditions. Inflation and unemployment have a negative relationship, the lower the level of unemployment, the higher the inflation rate. One of the causes of inflation is the increased price of goods which results in an increase in production costs. Whereas in Islam the existence of costs is caused by the monopoly of goods or labor, but in an Islamic-based market it is not applied. Therefore Muslim entrepreneurs will not face high costs to meet excess wages because workers get wages that must match the earned productivity. Furthermore, the handling of unemployment affected by the Covid-19 pandemic can be done by maximizing the Islamic economic philanthropic scheme, namely zakat, infaq, shadaqah, and lending on a qardhul hasan basis.